Workplace Conflict Factors and Employee Counterproductive Work Behaviour in Selected Private Universities in South-West Nigeria as Moderated by Organisational Justice - Worimegbe, Victoria; Makinde, Grace; Worimegbe, Powel; Nwankwere, Idowu; Egwuowun, Clara; Fesobi, Oluwaseun (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
Due to the increasing complexity in the job itself and the workplace in which it is performed, counterproductive work behaviour has attracted growing attention in recent years. While the existing literature has established that workplace conflict factors could be significant drivers of employees' counterproductive work behaviour, there has been a dearth of literature on this issue in academia. Therefore, this study examines the interactions between workplace conflict factors and employee counterproductive work behaviour using universities in South-West Nigeria as Moderated by organisational justice as the theatre of the study. The study relied primarily on questionnaires as its major data collection method, reflecting its adoption of a survey research strategy. The results revealed that workplace conflict factors do not affect employee outcomes in selected private universities in South-West Nigeria as moderated by organisational justice. This research suggests that universities that want to foster employee loyalty must develop and execute effective incentive systems.